Implementation of the Video Assistant Referee (VAR) as a Career Change-Event: The Israeli Premier League Case Study - Samuel, Roy David; Galily, Yair; Filho, Edson; Tenenbaum, Gershon (Frontiers in Psychology, 2020)
The inclusion of the video assistant referee (VAR) in the Laws of the Game (International Football Association Board; IFAB, 2018a) reflects a historic action in the world of soccer. The VAR was designed to reduce critical errors in soccer referees’ decision-making (DM), thereby increasing the social perceptions of justice. From the referees’ perspective, the implementation of the VAR represents a technical-technological career change-event (Samuel & Tenenbaum, 2011a). This case study adopted an intrinsic mixed-methods longitudinal methodology to investigate the implementation of the VAR system within the Israeli Premier League context. The referees perceived the VAR implementation as a moderate change-event and did not respond with acute emotional profile. The largest effects were in pre-match preparation, players’ management, public perception, and DM. The referees felt that their perceived pressure during the matches decreased. This change-event produced off-field demands mostly related to the educational process and on-field demands mainly related to developing VAR proficiency. The referees also experienced off-field (e.g., lack of clear goals and rewards system) and on-field barriers (e.g., errors of the VARs). To effectively cope with these new demands and barriers they made active decisions. They also received considerable support yet perceived their cooperation with the professional committee as moderate. The referees showed some professional improvements yet did not receive much appreciation. Thus, three of them perceived the outcome of this change process favorably, four naturally, and four negatively. The discussion presents reflections of these findings in light of the recently emerging literature on technological officiating aids in sport. Recommendations are provided for Referee Unions who aspire to integrate the VAR system into their operation.